Diel Vertical Migration of zooplankton in a eutrophic bay of Lake Victoria - Semyalo, Ronald; Nattabi, Juliet K.; Larsson, Petter (Hydrobiologia, 2009)
We studied the Diel Vertical Migration (DVM) of several zooplankton taxa and an important zooplanktivore Rastrineobola argentea in a eutrophic bay of Lake Victoria for a total of 3 months during wet and dry seasons. Zooplankton were sampled twice a month at full moon and new moon. The zooplankton community of this lake was numerically dominated by cyclopoid copepods ([80%) of which 80% were juveniles. The composition of zooplankton was not significantly different (P[0.05) for the different sampling months (November 2000, March 2001 and July 2001), but total zooplankton abundance was significantly lower (P\0.05) in July (dry season) than during March or November (wet seasons). DVM behaviour was observed in some of the zooplankton groups including Tropocyclops spp., Thermocyclops spp., Thermodiaptomus galeboides and Diaphanosoma excisum. In these groups, we also observed that they were significantly (P\0.05) more abundant at full moon than at new moon in some months, a pattern not seen in non-DVM groups. The amplitude of migration tended to be higher at new moon than full moon for all DVM zooplankton but not significantly so (P[0.05). The zooplanktivore R. argentea exhibits typical DVM behaviour, perhaps to avoid visual predation itself, but it also increases the predation pressure on zooplankton in deeper waters. Feeding times for R. argentea peak just after dusk and dawn. For the copepod calanoid T. galeboides, there was a strong relationship (P\0.05) between the amplitude of migration and midday (12:00) water transparency, suggesting that these zooplankton may have descended deeper on days with higher water transparency. In the absence of temperature and food gradients but with predation pressure from a migrating zooplanktivore, the depth of descent of zooplankton may be well associated with water transparency.
Keywords: Lake Victoria; Zooplankton; Diel Vertical Migration; Murchison Bay